Soil Compaction Curve of an Oxisol under Sugarcane Planted after In-Row Deep Tillage - Marasca, Indiamara [UNESP]; Lemos, Stella Vannucci [UNESP]; Silva, Reginaldo Barbosa [UNESP]; Sebastiao Guerra, Saulo Philipe [UNESP]; Lanas, Kleber Pereira [UNESP] (Soc Brasileira De Ciencia Do Solo, 2015)
Soil tillage that maintains the productivity of sugarcane plantations, providing an area for the root development and without traffic on crop rows, has given rise to new technologies in rural areas. The purpose of this study was to evaluate the soil physical properties in two sugarcane plantations, one of which was prepared with deep tilling and the other with conventional tillage. The experiment was conducted in Lencois Paulista, Sao Paulo State. Soil penetration resistance and relative density were analyzed. The cone index was lower in deep-tilled soil without traffic in all layers, than in deep-tilled soil with traffic and in conventional tillage. In both tillage treatments, the relative density values were acceptable in the 0.00-0.15 m soil layer, but considered detrimental for sugarcane development in the 0.15-0.30 and 0.30-0.45 m layers.
Keywords: soil management; soil tillage; subsoiler; traffic control system; Saccharum spp.